A particle of mass m moving with a velocity v makes an elastic one-dimensional collision with a stationary particle of mass m establishing a contact with it for extremely small time T. Their force of contact increases from zero to ...........?

A particle of mass m moving with a velocity v makes an elastic one-dimensional collision with a stationary particle of mass m establishing a contact with it for extremely small time T. Their force of contact increases from zero to F_0 linearly in time T/4, remains constant for a further time T/2 and decreases linearly from F_0 to zero in further time T/4 as shown in figure. The magnitude possesssed by F_0 is ?enter image source here

1 Answer
Mar 1, 2017

F_o = (4 m v)/(3T)

Explanation:

Momentum is always conserved so we can say -- where u_1, u_2 are the post-collision velocities of the first (previously moving) particle and the second (previously stationary) particle, respectively -- that:

mv = m u_1 + m u_2 implies v = u_1 + u_2qquad triangle.

From conservation of (kinetic) energy, we can say:

1/2 m v^2 = 1/2 m u_1^2 + 1/2 m u_2^2 implies v^2 = u_1^2 + u_2^2 qquad square

From triangle, we have:

u_2 = v - u_1 and so u_2^2 = (v - u_1)(v - u_1)

From square, we have:

u_2^2 = v^2 - u_1^2 = (v - u_1)(v+u_1)

implies (v - u_1)(v - u_1) = (v - u_1)(v+u_1)

implies v = u_1, u_2 = 0

or

implies v - u_1 = v+u_1 implies u_1 = 0, u_2 = v

From a consideration of the physical setup, we see that the only practical conclusion is that:

u_1 = 0, u_2 = v

The first particle cannot just move through the second particle with the second remaining stationary. Rather, all momentum and energy is transferred to the second particle.

We now turn to Netwon's 2nd Law: F = ma = m (dv)/(dt)

Because we have a Force-time graph, we can tweak the second law as follows, by integrating wrt time:

int_0^T F \ dt = int_0^T m (dv)/dt dt

We do this because we see that int_0^T F \ dt is the area of that graph, which is simply:

1/2 * T/4 * F_o + T/2 * F_o + 1/2 * T/4 * F_o = 3/4 T F_o

For the second integration, we change the integration variable (using the chain rule) to get:

int_0^T m (dv)/dt dt = m int_(v_1)^(v_2) dv

= m Delta v

Which here, because u_2 = v:

= m ( v - 0) = mv

Thus we can say that:

3/4 T F_o = m v

Or:

F_o = (4 m v)/(3T)